Lupin : discovery research - Sahay, Arvind; Tiwari, Tara; Kamboj, Raj; Vēṅkaṭa Subbārāvu, Paḷḷe; Sharma, Sharad (Sharad K.) (London : Indian Institute of Management, Ahmedabad, 2020)
Lupin, an India-based pharma firm, started its Novel Drug Discovery and Development (NDDD) division in 2010, for which it built infrastructure from scratch. In 2018, Lupin's NDDD successfully licensed MALT1 inhibitors to AbbVie, a multinational pharma firm, for a down payment of USD 30 million and progressive payments of USD 947 million over 10 years. This was the first success for this division. Going forward, Lupin had two programs in the clinical development stage. It now had to decide whether to go ahead with the clinical trials or license these two molecules as well.The case revolves around the organizational system and processes (industry-specific, company-specific) and market conditions that influence innovation and commercialisation of an innovation in the organization.
Description based on XML content.
Keywords: elektronické knihy; electronic books; Technological innovations -- Case studies; Marketing -- Management -- Case studies